Assessing the Effects of Parasitism and Predation by Water Mites on the Mosquitoes - Esteva, L.; Rivas, G.; Yang, H.M. (Trends in Computational and Applied Mathematics, 2007)
Water mites (Hydrachnidia) are a group of arthropods with a complex life cycle which includes larval and three nymphal stages. The mite larvae parasitize aquatic and semiaquatic insects, while deutonymphs and adult mites are predators of insect larvae and eggs. Since several families of water mites are associated with mosquitoes, there is an interest in the potential use of these mites as biological control agents of Aedes aegypti. The aim of this paper is to use mathematical modelling and analysis to assess the impact of predation and parasitism in the mosquito population by water mites. We discuss the fitness of water mites as biological control of mosquitoes by different scenarios that appear when we change the parasitism and predation parameters. High rates of parasitism and moderate predation can drive two species to a stable coexistence far from the extinction point.